Evolution and recent speciation in two disparate endemic South African insect genera: Macroderes (Coleoptera: Scarabaeidae) and Nemopterella (Neuroptera: Nemopteridae) - Sole, Catherine L. (University of Pretoria, 2024)
Thesis (PhD (Entomology))--University of Pretoria, 2019.